(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Prediction and forecast are common words in the area of election. It can also be related with word â€œopinion pollâ€. Although according to dictionary the meaning/definition of prediction is limited but practically prediction of election cannot be calculated under limited region. In general term, everybody is chipped with prediction. This relation may be direct or indirect. Prediction of weather, prediction about share market etc are few examples of prediction. Because of this, n numbers of predictions can be calculated. Are these accurate as compared to actual result? This is still a question having no suitable answer. To predict the result from election is again a wide concept. Majority of tools and models are there which are used to predict the result but still the area of social science or political science is not up to that level where others are. Due to its vague and imprecision, it is quite complex. The objective of this research is to design and develop a simple GUI model based upon FCM which can be used to calculate the prediction in the term of winning chances of a candidate before the actual result. The concept of fuzzy logic along with fuzzy cognitive maps (FCM) is used to determine the relation between various input parameters. An accurate and simple GUI is designed for this proposed model.